Research, design and fabrication of a high-power combiner using Wilkinson bridge of L-band - Dang, Thi Thanh Thuy (H. : ĐHQGHN, 2017)
In this paper, we are dealing with a L-band power combiner method using the Wilkinson bridge. This is a modem power combination technique in the microwave technology. The design and simulink of the basic power moduls and Wilkinson bridge were performed using the ADS soflware. We have researched, designed and fabricated the power combination from the basic 200W moduls. The experimental results showed that power combination method using the Wilkinson bridge may be applicable in the L-band transmission.